The effect of the information gap strategy on the acquisition of biological concepts and scientific sense among fifth-grade scientific students (Journal of the College of Basic Education, 2024)
The research aimed to identify the impact of the information gap strategy on the acquisition of biological concepts and scientific sense among students in the fifth scientific grade. To verify this, an experimental design was chosen, and the research population was represented by students in the fifth grade (biology) from Al-Rafidain Preparatory School for Boys, which was chosen by a simple random method, Section (C). The experimental group (32) students and Section (A) The control group (23) students for the academic year 2022/2023 AD The two research groups were rewarded in many variables. As for the research tools, the research prepared a test for the acquisition of biological concepts, consisting of (50 ) A multiple-choice item. In addition, the Scientific Sense Scale prepared by (Zahir, 2016) was adopted, which consists of (72) items. The validity and reliability of the two tools were verified. To verify the results, the researcher used a group of statistical methods. The results showed that teaching with a strategy The information gap helped the experimental group to acquire biological concepts and scientific sense compared to students in the control group. Accordingly, the researcher presented a number of recommendations and proposals .